Twenty-five years of school? Analysis of Free and Open Source software license texts (Journal of Open Law, Technology & Society, 2016)
The licenses of Free and Open Source Software are expected to be read and understood by all software users. Analysis of these texts shows that it is not an easily achievable goal.